ANALISA PROSES PENGUKURAN DAN TEST LOAD ALTERNATOR 35A, 60A DAN 100A DENGAN BEBAN BERVARIASI DI PT. U - charles pangaribuan; imran saputra (Jurnal Teknik Elektro Uniba (JTE UNIBA), 2019)
Abstract-The charging system is part of the electricity in the machine, in the fuel refueling system for full load conditions as well as must. In doing the Overhoul Alternator must be ascertained the condition of the components such as Stator, Rotor and Diode Rectifier in good condition. A good Stator and Rotor have a 35 Ohm coil Resistance and a minimum resistance of 0.5 Mohm.. In performing Test Load Alternator, to get a good test results required data varying each 25%, 50%, 75% and 100% of the capacitance of each alternator. Test Load process using DURST TB-1900A. Varitive loading is seen from the large Alternator output current in which every Alternator load must have a stable output voltage of 27.5 Volts - 28.5 Volts.From test load Alternator results obtained that Alternator with capacity 35 A and 100 A in good condition while for Alternator with the capacity 60 A is not in good condition.